Manajemen Pembelajaran al-Qirō’ah di Asrama - Wahidatun Choeriyah; Zuhdiyah Zuhdiyah; Ismail Sukardi (Studia Manageria, 2021)
Madrasah Aliyah Negeri 3 Palembang (Pondok al-Ihsan) is a non-formal educational institution that teaches more religious sciences, one of which is Arabic in al-Qirō'ah material. Al-Qirō'ah learning is one of the prioritized activities with the aim of producing outstanding students. In addition, al-Qirō'ah aims to understand the contents of the Qur'an and other Islamic sciences by using the grammatical method or Qawa'id. Good learning management is needed in al-Qirō'ah learning activitiesin order to achieve effective learning objectives. The formulation of the problem in this study is how to manage al-Qirō'ah learning which includes planning, implementation, monitoring and evaluation in the MAN 3 Palembang dormitory. This type of researchis a qualitative research, the key informant is the head of the dormitory. Collecting data using participant observation techniques, semi-structured interviews, and documentation. The final stages of data analysis are: data reduction, data presentation, and conclusions. In checking the validity of the data using triangulation. The results of the study indicate that: Al-Qirō'ah learning plans are arranged in the form of learning tools including annual programs, semester programs, syllabus and learning implementation plans. The implementation of al-Qirō'ah learning activities went well, namely the teachers taught according to the learning implementation plan. Supervision of al-Qirō'ah learning is carried out starting from monitoring, supervision, evaluation, reporting and follow-up. The evaluation carried out in the dormitory was quite good with the stages: daily tests, mid-semester exams and end-of-semester exams.